Pengaruh Leader Member Exchange dan Beban Kerja Terhadap Kinerja Pegawai yang Dimediasi oleh Kepuasan Kerja pada Badan Narkotika Nasional (BNNP) Provinsi Maluku - Ririnama, Alisa; Risambessy, Agusthina (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2024)
The Influence of Leader Member Exchange and Workload, on employee performance mediated by job satisfaction at the National Narcotics Agency of Maluku Province. This study discusses how the influence of Leader Member Exchange and Workload on employee performance mediated by job satisfaction at the National Narcotics Agency of Maluku Province. The purpose of this study is to test and analyze the Influence of Leader Member Exchange on Employee Performance, the Influence of Workload on Employee Performance, the Influence of Leader Member Exchange on Job Satisfaction, the Influence of Workload on Job Satisfaction, the Influence of Job Satisfaction on Employee Performance, the Influence of Leader Member Exchange on Employee Performance mediated by job satisfaction, the Influence of Workload on Employee Performance mediated by job satisfaction. This study was conducted using a questionnaire distributed with a total sample of 34 using a non-probability sampling technique and the analysis method used in this study is the Structure Equation Model using smartPLS 3. Based on the results tested, it shows that the influence of leader member exchange is positive and not significant on employee performance with P-value = 0.042 <0.05, then the influence of workload is positive and significant with P-value = 0.196> 0.05, and the influence of leader member exchange and workload does not have a positive and significant influence with P-value = 0.112> 0.05 on performance with job satisfaction as a mediator. So it can be concluded that with or without job satisfaction as a mediating variable will not affect performance.